Studies on the insect pollination of fruit tree species and on closely related topics in Hungary: a bibliography of research publications - Benedek, P. (International Journal of Horticultural Science, 2000)
In the past decades fruit production has become more and more intensive and so the interest towards the bee pollination of fruit trees has increased in Hungary. Thus insect pollination research has become more intensive in the eighties and in the nineties. Recently, high density fruit orchards are planted of dwarf trees at more and more farms in Hungary and these need highly controlled growing practices involving insect pollination, too. This is a new challenge of insect pollination research in Hungary. So it seems to be worth to compile a list on research publications having been appeared so far to create a basis to the ongoing new research. Besides papers strictly on the insect pollination of fruit trees publications on some closely related topics, first of all on the nectar production and on other flower characteristics of fruit tree cultivars that directly influence bee activity have also been included on the list.